(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Knee osteoarthritis is a common degenerative joint disorder strongly influenced by mechanical and metabolic factors. Body Mass Index is an important modifiable risk factor that may influence both the onset and severity of knee osteoarthritis. Aim: To evaluate the correlation between Body Mass Index and severity of knee osteoarthritis in a cross-sectional study. Materials and Methods: This study was a hospital-based cross-sectional observational study conducted in the Department of Orthopaedics of a tertiary care teaching hospital over a period of 1 year. The study population included 100 patients diagnosed with knee osteoarthritis attending the outpatient department during the study duration who met the inclusion criteria. The main objective of the study was to evaluate the correlation between Body Mass Index and severity of knee osteoarthritis. Results: In the present study, a total of 100 patients with knee osteoarthritis were analyzed to determine the association between gender and severity of disease. Among male patients (n = 55), 28 patients (50.9%) had mild osteoarthritis, 15 patients (27.3%) had moderate disease, and 12 patients (21.8%) had severe osteoarthritis. Among female patients (n = 45), 24 patients (53.3%) had mild disease, 11 patients (24.4%) had moderate disease, and 10 patients (22.2%) had severe osteoarthritis. No statistically significant association was found between gender and severity of knee osteoarthritis the p-value was 0.41. Conclusion: Increased Body Mass Index is significantly associated with greater severity of knee osteoarthritis. Weight reduction may play an important role in preventing progression and improving clinical outcomes in knee osteoarthritis patients.